Purification and Concentration of Caustic Mercerization Wastewater by Membrane Processes and Evaporation for Reuse - Tunc, M. Sara; Yilmaz, Levent; Yetis, Ulku; Culfaz-Emecen, P. Zeynep (Taylor & Francis Inc, 2014)
A membrane-based treatment strategy was developed for purifying the highly alkaline textile mercerization wastewater. 0.2-mu m MF and 100 kDa UF membranes were evaluated as pretreatment alternatives before 10 kDa UF and 200 Da NF membranes. Turbidity was almost totally removed by both pretreatment options, while UF (100 kDa) showed higher COD retention than MF. In total recycle mode of filtration, fouling of both UF and MF membranes were 80% reversible by physical and almost totally reversible (>= 97%) by chemical cleaning. In the second stage filtrations applied to the pretreated wastewater samples, NF could yield high (97-98%) COD retentions and low permeate COD concentrations (<= 22 mg/L), while 10 kDa UF could only reduce the COD concentration to 150 mg/L. While no NaOH was lost in the MF+UF process, the use of NF as second stage resulted in 12-17% NaOH retention. The permeate flux in all second stage processes were stable, implying that the majority of the feed components that would cause fouling had been removed in the pretreatment stages. Permeate of the MF+NF sequence was concentrated by evaporation with no foaming problems, showing that the hybrid process can be applied to recycle a purified and concentrated caustic stream to the mercerization process.
Keywords: microfiltration; ultrafiltration; nanofiltration; caustic textile wastewater; reuse